Role of Histone Deacetylase 9 in premature aging of the lung during chronic inflammation - Avci, Edibe; Justus Liebig University Giessen (My University, 2023)
Age-related lung diseases are a growing public health issue globally, especially chronic lung diseases in older individuals. Environmental factors, including epigenetic changes, contribute significantly to cellular aging, though the exact mechanisms are unclear. Our histological analysis shows that removing HDAC9 alters pulmonary surfactants and reduces lung cell regeneration, leading to decreased cell proliferation. HDAC9 depletion also reprograms AT2 cells into new mesenchymal-like cells and induces cellular senescence, with these senescent AT2 cells showing a SAS phenotype. This includes increased expression of p21, SA-β-GAL, pro-inflammatory cytokines, and metalloproteinases compared to age-matched controls. HDAC9 deficiency in aged mice further exacerbates these changes, including BALT formation characterized by T cells and Iba1+ macrophages. High-throughput studies revealed that HDAC9 deficiency alters the cellular composition of aged lungs, reducing CD117+ and EpCAM+ epithelial cells and increasing adaptive immune cells. RNA sequencing indicated that HDAC9 influences metabolic pathways in aging AT2 cells, particularly affecting the phospholipase A2 family. Metabolic profiling showed reduced choline in young HDAC9 KO-AT2 cells and disrupted choline conversion in aged cells, with elevated pro-inflammatory metabolites in aged HDAC9 KO-AT2 cells. In vitro studies indicated that HDAC9 deficiency affects BM-derived macrophages, with inflammatory and anti-inflammatory genes upregulated in M1 and M2 macrophages, respectively. AMs also showed higher proliferation when exposed to media from HDAC9-deficient AT2 cells. Lipidomic analysis revealed higher linolenic acid in HDAC9-depleted M1 macrophages. In conclusion, HDAC9 deficiency leads to premature aging and a secretory phenotype in AT2 cells, releasing pro-inflammatory lipid mediators like prostaglandins. These mediators attract immune cells, primarily T cells, leading to BALT formation in the lungs.
Keywords: 610